Visiting the Big Fresno County Fair - Watkins, Howard::::::::: (1981)
Fresno County Young Lawyers Legal Information Booth with brochure display; Channel 18 "Know Your Rights" Personal Injury program playing on portable television (Richard Watters and Colin Daugherty on screen)